ANALISIS IMPLEMENTASI METODE BERNYANYI UNTUK MENSTIMULASI MINAT BELAJAR BAHASA ARAB SISWA DI MADRASAH IBTIDAIYYAH NURUL YAQIN SUNGAI DUREN - Kelvin SyahLimnata; KA Rahman; Mar'Atun Sholiha; Mulyadi Mulyadi; Neldi Harianto (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Arabic language learning in Islamic elementary schools often faces challenges due to students’ low learning interest, caused by monotonous conventional methods and limited learning media. This study aims to describe the implementation of the singing method (thariqah al-ghina'iyyah) in Arabic learning for Grade 5A at MI Nurul Yaqin Sungai Duren and to analyze how this method stimulates students’ learning interest. This research employed a qualitative descriptive approach involving 24 students, one Arabic teacher, and the school principal. Data were collected through participatory observation, semi-structured interviews, and documentation studies. Data analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the singing method was implemented in three stages: preparation, implementation, and follow-up, applying principles of contextualization, differentiation, and interactivity. The method functions as a multimodal stimulus that lowers the affective filter, strengthens vocabulary memory through dual coding, and fulfills students’ psychological needs for competence, relatedness, and autonomy. The results show a significant increase in learning interest, reflected in students’ enthusiasm, active participation, and attentiveness.